1976
DOI: 10.1021/je60069a034
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric constants, viscosities, and related physical properties of several substituted liquid ureas at various temperatures

Abstract: Dielectric constants, viscosities, densities, and refractive indices of three urea derivatives were measured at various temperatures ranging from 25 to 100 °C. The experimental data as functions of temperature were fitted precisely to appropriate equations. Dielectric constant data indicated a significant increase in dielectric constant of the cyclic ureas over that of the acyclic homologs. Kirkwood correlation factors and the activation energies of viscous flow were also evaluated. Values for Kirkwood correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 16 publications
(36 reference statements)
3
25
0
Order By: Relevance
“…Recently 1,3-dimethylethyleneiirea (DMEU) has been investigated with regard t o somc of its fundamental properties (0) and to the behavior of electrolytes therein (7,8). It was found that DMEU is a solvent of high polarity (4.09 in dioxane) (9), moderately high dielectric constant (37.6 at 1 MHz) (6). and possesses good dissociative power towards electrolytes, comparable to that of hr-methyl-2-pyrrolidone and methanol.…”
mentioning
confidence: 99%
“…Recently 1,3-dimethylethyleneiirea (DMEU) has been investigated with regard t o somc of its fundamental properties (0) and to the behavior of electrolytes therein (7,8). It was found that DMEU is a solvent of high polarity (4.09 in dioxane) (9), moderately high dielectric constant (37.6 at 1 MHz) (6). and possesses good dissociative power towards electrolytes, comparable to that of hr-methyl-2-pyrrolidone and methanol.…”
mentioning
confidence: 99%
“…Alkan-1-ols are self-associated through hydrogen bonding and a DMI molecule interacts strongly with another DMI molecule through dipole-dipole interactions because of its high dipole moment: ca. 4.09 D (D % 3.335640952 AE 10 À30 C AE m) [1]. A mixing of DMI with an alkan-1-ol brings about not only the disruption of hydrogen bonding among alkan-1-ol molecules but also that of dipole-dipole interactions between two DMI molecules, which lead a positive contribution to volume.…”
Section: Resultsmentioning
confidence: 99%
“…1,3-Dimethylimidazolidin-2-one (DMI) is one of the cyclic ureas and a versatile dipolar aprotic solvent [1,2]. Limited studies on physical properties of pure DMI have been carried out and only two reviews on the properties are available in the literature [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The chemicals used, their suppliers and purities, together with the experimental and literature densities (10,11) are listed in table 1.…”
Section: Methodsmentioning
confidence: 99%